Memristors: Direct Observation of Localized Radial Oxygen Migration in Functioning Tantalum Oxide Memristors (Adv. Mater. 14/2016). Issue 14 (April 2016) - Kumar, Suhas; Graves, Catherine E.; Strachan, John Paul; Grafals, Emmanuelle Merced; Kilcoyne, Arthur L. David; Tyliszczak, Tolek; Weker, Johanna Nelson; Nishi, Yoshio; Williams, R. Stanley
Abstract : As information bits of 0's and 1's are stored in crosspoint tantalum oxide memristors, or resistive random access memory (RRAM) cells, nanoscale‐resolution in operando X‐ray transmission spectromicroscopy is used by J. P. Strachan and co‐workers, as reported on page 2772, to directly observe oxygen migration and clustering, revealing an important operation and failure mechanism of RRAM, a frontrunner technology for next‐generation computer memory.